The sorting of female careers after first birth: a competing risks analysis of maternity leave duration - Arntz, Melanie; Dlugosz, Stephan; Wilke, Ralf A. (Oxford bulletin of economics and statistics, 2017)
A number of contributions have found evidence that motherhood is a critical life event for women's employment careers. This study presents a detailed analysis for the duration of maternity leave in which young mothers can make a transition into different types of employment, unemployment as well as the next birth. We provide a comprehensive picture of the sorting mechanisms that lead to the differentiation of women's employment careers after birth. Our empirical evidence is derived from large-linked administrative individual labour market data from Germany for a period of three decades. We obtain unprecedented insights into how women's skills, the quality of the previous job match, firm level characteristics, labour market conditions and leave legislation are related to the length of maternity duration. Expansionary leave policies, e.g. are found to be a key factor for the rising share of women who have their second child out of inactivity.
Gesehen am 16.08.2018